Intratypic variations among Thai Herpes Simplex Virus (HSV) isolates determined by Restriction Fragment Length Polymorphism (RFLP) analysis - Sutida Visaprom (2018)
Whole genomic polymorphisms for 20 HSV-1 and 20 HSV-2 isolates from Thai patients were analyzed by means of Restriction Fragment Length Polymorphism (RFLP) analysis using 4 restriction endonucleases: BamHI, KpnI, HindIII, and EcoRI. Variations in cleavage sites among the HSV-1 and HSV-2 isolates were compared to the cleavage patterns of standard HSV-1 strain KOS and HSV-2 strain Baylor 186. Although 70% of HSV-1 isolates with BamHI digestion, 50% with KpnI, 75% with HindIII and 70% with EcoRI digestion were found to be similar to the standard HSV-1 (KOS) pattern, new BamHI restriction sites were detected in some HSV-1 isolates. For HSV-2 isolates, 85% had the same pattern as the standard HSV-2 (Baylor 186) after digestion with BamHI, HindIII, and EcoRI. No difference was observed with KpnI digestion. When the patterns from the 4 enzymes were combined, HSV-1 isolates showed more divergence than the HSV-2 isolates. HSV-1 isolates found in both non-genital and genital lesions had more variety than the HSV-2 isolates. This suggests that intratypic variations in HSV-2 are fewer than in HSV-1.